The education systems of Europe - Hörner, Wolfgang [Herausgeber]; Döbert, Hans [Herausgeber]; Reuter, Lutz R. [Herausgeber]; Kopp, Botho von [Herausgeber] (Springer International Publishing, 2015)
This volume presents an analytical description of the education systems and their developments of all European countries from a comparative perspective. The country contributions follow common guidelines - exceptions are only to be found for the smaller European nations. "These conceptual guidelines consider various criteria concerning presumptions as to the quality of a good education system. One of the book's central aims is to explore the paradoxical character of education, i.e. the relationship between universal values and the search for a national identity. The concept behind this volume focuses on the link between descriptive representation and problem-oriented analysis. The individual country contributions have been structured to highlight historical developments; to describe national problems; to broach issues relevant to the organization of the respective general and vocational education system in the context of ongoing discussions; and to spotlight development prospects for the country in question." The concept of "Europe" in the volume is wide-reaching and goes far beyond an EU perspective. It covers in total 50 sovereign states in Europe (mainly the member states of the Council of Europe). (Editor, BIBB-Doku)
Keywords: T 1.5 International vergleichende Berufsbildungsforschung; S 1 Stufen der Berufsbildung; I 2.2 Europa; Vergleichende Bildungsforschung; Bildungssystem; Historische Entwicklung; Bildungspolitik; Bildungsreform; Internationaler Vergleich; Europa